Locational analysis of socioeconomics and tax aspects on soybean production in Mato Grosso (Revista Teoria e Evidência Econômica, 2012)
This paper has as main intent to evaluate the soybean production considering aspects such capacity of work generation, income, and the ICMS collected on Mato-grossenses cities. It is common knowledge that there are plenty of papers on the subject, but, not all aspects were studied or even correlated. The methodology proposed on this paper correlates the soybean production income with the work generation and ICMS collected, through a local specialization index that usually is used to delimitate to localization of some economic activity. This indicator, graphically plotted, allows us to identify if there is any abnormality in the structure of collection or in formal employment. Specifi cally in the case of Mato Grosso, 44 municipalities were selected as specialized and as expected, the graph of income was more stable, while the employment and revenue showed most signifi cant changes, identifying situations that may suggest distortion of the record of employees and payment of ICMS. With regard to employment, some municipalities had a very high specialization in the register of employees, which clashes with the generation of income, but that confi rms the formalization of employment. The same does not occurs with the collection of ICMS, where many municipalities recorded a higher specialization of the income and others lower and both situations cause problems in the revenue distribution for the regions. Although it is a systemic fact, the allocation of public resources is compromised and the regional inequalities may be being encouraged by government itself.Keywords: Employment. ICMS. Income. Mato Grosso. Soybean.